Comprehensive description of T2 value spatial variations in non-osteoarthritic femoral cartilage using three-dimensional registration of morphological and relaxometry data - Edd, Shannon N.; Babel, Hugo; Kerkour, Nadia; Jolles, Brigitte M.; Omoumi, Patrick; Favre, Julien (The knee, 2019)
The aim of this study was to develop and assess a method of quantifying cartilage T2 relaxation times in a series of volumes of interest (VOIs) covering the entire cartilage of the femoral condyles. Subsequently, the method was used to test for T2 spatial variations in non-osteoarthritic (OA) knees. Ten non-OA subjects (five female, average 30 years) were enrolled after informed consent. Three-dimensional bone and cartilage models were created by double echo steady state (DESS) morphological magnetic resonance image (MRI) segmentation, and the models were semi-manually registered with multi-slice, multi-echo (MSME) T2 MRI. Mean T2 values were calculated for 12 VOIs derived from cartilage thickness literature and their respective superficial and deep layers. Analyses showed that intra- and inter-rater reliabilities of the presented method were “good” to “excellent” in more than 90% of the VOIs. Additionally, several spatial differences in T2 values were observed, including, for the medial condyle, higher T2 values in the anterior and central VOIs versus in the posterior VOI (p < .05). T2 values were also generally higher in the superficial versus deep layers (p < .05). The presented MRI T2 analysis method is reliable and provides a comprehensive quantification of spatial heterogeneity of healthy cartilage compositional properties. This method can be further applied to better understand knee OA pathophysiology and potentially define clinically relevant diagnostic features of the disease.